2020
DOI: 10.3390/su12187610
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Motives for Online Fashion Renting: Insights from Social Retailing to Sustainability

Abstract: Despite the exponential growth of collaborative consumption practices, online fashion renting, an important type of collaborative fashion consumption, is still underexplored. Drawing on the theories of Reasoned Action (TRA) and Innovation Diffusion, we developed a holistic research framework to explore the motives for online fashion renting. By analyzing a total of 300 usable responses collected by a research market company using structure equation modeling (SEM), we found that attitudes and subjective norms p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 70 publications
(143 reference statements)
4
29
1
Order By: Relevance
“…Normative motives. Normative motives have been the subject of recent research, and previous studies have found a positive relationship between normative pressure and the intention to purchase online [49,59,[62][63][64][65]. We argue that during the COVID-19 pandemic, normative pressure has been an important determinant of the intention to purchase online.…”
Section: Hypothesis Developmentmentioning
confidence: 63%
“…Normative motives. Normative motives have been the subject of recent research, and previous studies have found a positive relationship between normative pressure and the intention to purchase online [49,59,[62][63][64][65]. We argue that during the COVID-19 pandemic, normative pressure has been an important determinant of the intention to purchase online.…”
Section: Hypothesis Developmentmentioning
confidence: 63%
“…Becker-Leifhold [14] highlights that customers could positively evaluate their rental experience even in terms of ease of accessing the service. Even if the customers' personal experience during the service represents one of the main drivers, Lee and Huang [18] and Becker-Leifhold [14] also focus on others' experiences: for instance, customers are naturally influenced by external feedback, such as reviews and Word Of Mouth (WOM), especially from close friends or family. Lee and Chow [19] add that others' experiences highly influence customers' intentions to rent fashion items, especially for individuals who have never tried renting before.…”
Section: Item Damagementioning
confidence: 99%
“…Consumer motivations to engage in PSSs both generally and specifically in fashion rental PSSs have been studied, with general agreement that the majority of fashion rental consumers primarily value the economic and functional benefits of the system [25,26,29]. Other non-monetary intangible perceived consumer benefits of the rental system include a desire for change and new experience, social aspects of the model and the relative advantage of access to garments for fashion-conscious consumers [24,29,[37][38][39]. There remains, however, a gap in knowledge regarding how fashion rental PSS providers view the value creation aspect of their offer, and what motivates them to continue in this space.…”
Section: Pss Fashion Modelsmentioning
confidence: 99%
“…Hence, this study offers a taxonomy for mutual benefit exchange in fashion rental PSSs, with the aim of providing future pathways to stabilise this alternative consumption model within the fashion system (Figure 3). Prior literature has identified a significant consumer drive toward the non-monetary, intangible benefits of renting in the emerging fashion apparel world [24,29,[37][38][39], including the social benefits of consumption communities. A conscious system design that embraces this within fashion PSSs would have a significant advantage over existing models in the apparel rental market.…”
Section: Conclusion: Toward a Benefit Exchange Taxonomy For Fashion R...mentioning
confidence: 99%